Chitinase 3-like 1 is not a target antigen in patients with multiple sclerosis. (August 2021) - Comabella, Manuel; Deutschmann, Claudia; Midaglia, Luciana; Schierack, Peter; Martínez, Júlia; Roggenbuck, Dirk; Montalban, Xavier
Autoimmunity to chitinase 3-like 1 (CHI3L1) has recently been reported in hepatic and bowel inflammatory conditions. Considering that CHI3L1 plays a role as prognostic biomarker in multiple sclerosis (MS), here we investigated CHI3L1 as potential autoantigenic target in the disease. We determined serum CHI3L1 autoantibodies by enzyme-linked immunosorbent assay (ELISA) in a cohort of 60 untreated MS patients with different clinical forms of the disease and 20 healthy controls (HC). IgG levels to CHI3L1 were similar between patients with relapsing-remitting MS, primary and secondary progressive MS, and HC. These findings do not support a role for CHI3L1 autoantibodies in MS pathogenesis.